GE_GERICHTE P/11156/2008 vom 8. Juni 2015 - GE Cour de justice (2015)
SÛRETÉS; CONFISCATION(DROIT PÉNAL); CRÉANCE; ALLOCATION AU LÉSÉ; INDEMNITÉ(EN GÉNÉRAL); RESTITUTION(EN GÉNÉRAL) | CPP.239.1; CPP.239.2; CPP.239.1.c; CPP.433; CPP.135; CP.69; CP.70; CP.71; CP.73.1.c; CP.73.3; CP.71.2